KONSTRUKSI GENDER DALAM MEDIA MASSA (ANALISIS SEMIOTIKA PIERCE PADA PROGRAM MATA NAJWA EPISODE â€œGENGSI BEREBUT KURSIâ€) - Primasari, Winda (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2017)
There is a notion that women belong only in domestic area. This biased perspective is still applied in our community. The perspective that women serves the domestic area instead of public area is constructed and sharpened by the mass media. This research aims to find out how the mass media potrays women who serve in the public area, especially female politician. Using Pierce?s semiotic, the findings show that the gender contruction build by the mass media can be considered as bias and misleading